2021
DOI: 10.3390/polym13193386
|View full text |Cite
|
Sign up to set email alerts
|

Rosin-Based Epoxy Vitrimers with Dynamic Boronic Ester Bonds

Abstract: Rosin is an abundantly available natural product. In this paper, for the first time, a rosin derivative is employed as the main monomer for preparation of epoxy vitrimers to improve the mechanical properties of vitrimers. Novel epoxy vitrimer networks with dynamic reversible covalent boronic ester bonds are constructed by a reaction between thiols in 2,2′–(1,4–phenylene)–bis (4–mercaptan–1,3,2–dioxaborolane) (BDB) as a curing agent and epoxy groups in the rosin derivative. The rosin-based epoxy vitrimer networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…[ 167 ] Up to date, two studies report the preparation of partially biobased vitrimers from fossil‐based 2,2’‐(1,4‐phenylene)‐bis[4‐mercaptan‐1,3,2‐dioxaborolane and a rosin‐based diepoxide or epoxidized soybean oil acrylate. [ 168,169 ] To the best of our knowledge, no study with higher renewable content was published.…”
Section: Other Dynamic Covalent Chemistriesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 167 ] Up to date, two studies report the preparation of partially biobased vitrimers from fossil‐based 2,2’‐(1,4‐phenylene)‐bis[4‐mercaptan‐1,3,2‐dioxaborolane and a rosin‐based diepoxide or epoxidized soybean oil acrylate. [ 168,169 ] To the best of our knowledge, no study with higher renewable content was published.…”
Section: Other Dynamic Covalent Chemistriesmentioning
confidence: 99%
“…Avérous and colleagues [ 159] Ad3 Am1 Catalyst-free −10 soybean oil acrylate. [168,169] To the best of our knowledge, no study with higher renewable content was published.…”
Section: -16mentioning
confidence: 99%
“…When the relaxation times were applied in an Arrhenius plot, a linear relationship was observed as shown in Figure d, and the activation energy was calculated to be around 36 ± 1 kJ mol –1 . Interestingly, the calculated activation energy was lower than the reported activation energies of either solely used boronic esters or imine bonds (38–157 kJ mol –1 ) as the dynamic cross-links. It could be deduced that this combination of two DCBs (boronic esters, imine bonds) was much more efficient than the sole one in term of stress relaxation.…”
Section: Resultsmentioning
confidence: 56%
“…180 Zeng et al reported rosin-based epoxy vitrimers with dynamic boronic ester bonds. 181 A rosin derivative–fumaropimaric acid (FPA) was synthesized via modifying rosin with fumaric acid and then reacted with epichlorohydrin to obtain a rosin-based epoxy monomer (FPAE). FPAE was cured with 2,2-(1,4-phenylene)-bis(4-mercaptan-1,3,2-dioxaborolane) (BDB) to fabricate an epoxy vitrimer via the reaction between thiols and epoxy groups (Fig.…”
Section: Biobased Cansmentioning
confidence: 99%